Assessment of Functional Communication in a Healthy-Aging Older Adult (The Review of Diabetic Studies, 2024)
This case study investigates the functional communication capabilities of an 82-year-old individual with a university-level education in teacher training and a 40-year career in education. Currently retired, the participant maintains an active lifestyle across the physical, cognitive, social, and spiritual domains. The patient had a history of hypertension and a family history of metabolic and cardiovascular diseases. The assessment adhered to current national and international ethical guidelines, employing interviews and validated instruments, such as the Communication Assessment Form for Older Adults and Salazar's protocol (2022), grounded in a biopsychosocial perspective. The findings revealed a well-preserved functional communication profile with intact basic and higher-level communication skills. The subject demonstrated effective verbal interaction, appropriately adapting to context and interlocutor, utilizing relevant linguistic and nonverbal resources, and employing compensatory strategies to address mild hearing and technological challenges. Overall, performance reflects healthy, autonomous, and socially integrated communication skills in later life.